DSM-5 diagnosis in the schools - Tobin, Renee Margaret; House, Alvin E. (New York The Guilford Press, 2016)
"Thousands of practitioners using prior versions of DSM have relied on this key resource to optimize their diagnostic practices in PreK-12 settings. Now significantly revised for DSM-5, the book cuts through the overwhelming length and complexity of the diagnostic manual by focusing thematically on the most common child and adolescent concerns. Tips are provided for diagnostic decision making and coding, and technical terms are demystified. Emphasis is given to using diagnosis as a foundation for effective intervention. The book highlights links to special education eligibility under IDEA and discusses ethical and professional issues in school-based assessment. New to This Edition *Revised throughout for DSM-5. *Restructured chapters on learning, communication, and motor problems; mood problems; anxiety problems; conduct problems; and impulse-control problems. *Updated content on IDEA 2004. *DSM-IV-TR Notes encapsulating changes to each set of diagnostic criteria. *Author Commentary sidebars sharing clinical insights and experiences"--Provided by publisher.
"Efficient and accurate use of the American Psychiatric Association's (2013) Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) has become a necessary part of the professional duties of psychologists in a variety of clinical, rehabilitative, and child service agencies. This book is intended to increase child psychologists' familiarity with DSM-5 and to bolster their confidence in using it within school settings. The present text attempts to provide a broad understanding of the DSM-5 system--what it attempts to do, how it is organized, and how to use it most effectively to capture and communicate the unique features of children's and adolescent's problems."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Diagnostic and statistical manual of mental disorders; Child psychopathology -- Diagnosis; Adolescent psychopathology -- Diagnosis